PENGARUH TINGKAT PENGUNGKAPAN CSR DAN MEKANISME GCG PADA KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN - Karjaya, I Wayan Hendra; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 8 No 3 (2014), 2014)
The purpose of this study is to determine the effect of the level of corporate social responsibility disclosure and implementation of good corporate governance mechanism on the financial performance of mining companies listed on the Indonesia Stock Exchange for the period of 2008-2012. The sample research consists of 14 out of 37 mining companies listed, which are determined by purposive sampling method. The data are collected using non-participant observation, which are then analyzed using multiple linear regression. The results show that CSR has a positive effect on the company's financial performance, whereas not all of three proxies of GCG positively affect the financial performance. Independent board of commissioners and institutional ownership have no effect on financial performance, however, managerial ownership shows a positive effect on the company's financial performance. CSR disclosure is necessary to prevent external costs that affect the company's financial performance. In addition, good corporate governance mechanism will also be able to help improving the company's financial performance.
Keywords: corporate social responsibility, good corporate governance